Travel and tourism in Britain, 1700-1914.
1 online resource (2048 pages).
Keywords: The British led the way in holidaymaking. This four-volume primary resource collection brings together a diverse range of texts on the various forms of transport used by tourists, the destinations they visited, the role of entertainments and accommodation and how these affected the way that tourism evolved over two centuries. Volume 3: Seaside Holidays Over the course of the seventeenth century, medical writers and practitioners came to realise the health-giving properties of the seaside environment. By the early eighteenth century, this scientific interest was spreading to wealthy people in search of a rest cure. Bathing in the sea, drinking the waters and spending time in the bracing air became a widespread activity, and by the nineteenth century this had expanded thanks to extensive advertising and publicity about its beneficial effects. Specific forms of entertainment also developed, such as piers, aquaria, winter gardens and cinemas.